Core-section summary for IODP Site 389-M0106 - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
List of recovered core sections from the above given site of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs) during the offshore phase of this expedition. The offshore phase took place between 2023-08-31 and 2023-10-31 onboard multipurpose vessel MMA Valour sailing from and to Barbers Point Harbor, Hawai extquotesinglei, USA. Cores have been acquired by Benthic extquotesingles fifth-generation Portable Remotely Operated Drill (PROD5). Following IODP convention, the 2.75 m liners extracted from each core barrel were cut into one or two sections (depending on core recovery) with a maximum section length of 1.5 m. Two types of liner were used during Expedition 389; Aluminum and polycarbonate liners, each requiring different treatment at this initial stage. Material recovered from the core catcher is treated as a separate section labelled "CC" for core catcher and placed below the last section recovered from the core barrel. The IODP standard naming of sections includes the following information: expedition number, hole, core, core type and section. For example, a section label (column Sample label) 389-M0097A-15R-2 represents section 2, core 15R (R indicating the core has been recovered by rotary coring method), from Hole M0097A during Expedition 389. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025